Unused, leftover and expired medicine and disposal practices among health sciences faculty students in Burdur, Turkey - Koksoy, Serkan (Journal of the Pakistan Medical Association, 2024)
Objective: To evaluate the opinions of university-level Health Sciences students about unused, leftover and expired medicine, as well as their disposal practices, and to classify the medicines. Methods: The cross-sectional study was conducted from April 1 to May 31, 2023, at the Faculty of Health Sciences, Burdur Mehmet Akif Ersoy University, Turkey, and comprised those studying at the Nursing, Nutrition Dietetics and Physical Therapy and Rehabilitation departments. Data was collected using Google Forms. The Anatomical Therapeutic Chemical classification was used for classifying pharmaceutical active ingredients. Data was analysed using SPSS 24. Results: Of the 373 participants, 272(73%) were females and 101(27%) were males. The overall mean age was 20.8±2.8 years. There were 348(93.3%) subejcts who reported having a total of 845 boxes of leftover and unused medicines in their homes (2.3±1.9 per capita), while 25(6.7%) participants had none. The medicines were stored in the kitchen 261(61.5%) as the storage area, and in the refrigerator 181(40.2%) as the storage unit. The expired medicine was disposed of in the garbage in 328(86.1%) cases. Self-medication was prevalent in 325(87.1%) cases. Anatomical Therapeutic Chemical classification analysis showed that paracetamol, acetylsalicylic acid, paracetamol+caffeine and metamizole sodium was the most common group of leftover and unused medicines 283(81.3%) Conclusion: High prevalence of unused and leftover medicine, disposal of medicine in household garbage, and self-medication behaviour indicated a serious public health and environmental problem. Key Words: Pharmaceutical, Public health, Self-medication, Turkey.